Leadership development for technical and vocational education and training college leaders in South Africa : a post-graduate curriculum framework - Robertson, Catherine Anne; Du Plessis, Catherine Anne (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch, 2015.